Photocurable Polymeric Blends for Surgical Application - Cernadas, Teresa (2021)
The preparation of photocrosslinkable bioadhesives synthesized from oligomers of lactic acid and polycaprolactone (PCL), both functionalized with 2-isocyanoethyl acrylate (AOI), were studied. The obtained modified macromers of LA-AOI (mLA) and PCL-AOI (mCL) were chemically characterized by 1H NMR and used to formulate polymeric blends with different mass proportions, 1:1, 1:2 and 2:1, respectively. Subsequently, the produced blends were crosslinked, considering two UV irradiation times: 30 and 120 s. After their production, the thermal and mechanical properties of bioadhesives were assessed, where upon the rheology, gel content, hydrolytic degradation and dynamic contact angles were determined. Furthermore, the cytotoxic profile of bioadhesives was evaluated in contact with human dermal fibroblasts cells, whereas their antibacterial effect was studied monitoring Escherichia coli and S. aureus growth. Overall, flexible and resistant films were obtained, presenting promising features to be used as surgical bioadhesives.